Moderating effect of work‐related social support on the relationship between role conflicts and job satisfaction among female nurses pursuing a further degree in China. Issue 5 (12th September 2021) - Li, Caifu; Song, Rhayun; Fan, Xing; Zhou, Zanhua; Xu, Lijuan
Abstract: Aim: This study aimed to determine the moderating effect of work‐related social support on the relationship between work–family–school role conflicts and job satisfaction among female registered nurses pursuing further degrees in China. Methods: The study had a cross‐sectional correlational design. Convenience sampling was applied to recruit participants from eight hospitals in China from January to August 2017. SPSS software and the PROCESS macro were used to conduct the data analyses in the present study. Results: A total of 320 nurses were included in the present study. Work–family–school role conflicts were negatively correlated with job satisfaction ( r  = −0.21, P  < 0.001). Work‐related social support was a significant moderator (interaction effect: β  = 0.22, P  = 0.039) on the relationship between work–family–school role conflicts and job satisfaction. Conclusions: The study revealed that when nurses perceived that they received a low or moderate level of social support in the workplace that strengthened the relationship between work–family–school role conflicts and job satisfaction. Hospital administrators should implement school‐ and family‐friendly policies that increase the social support provided to nurses pursuing further degrees to balance their responsibilities of work, family and school and to improve their job satisfaction. Summary statement: What is already known to the topic? Registered nurses pursuing further degree perform multiple roles in their lives at work, at home and at school, leading to work–family–school role conflicts. Work–family conflict was significant related with job satisfaction among registered nurses. Social support played a role as a moderator in the relationship between work–family conflict and mental health. What this paper adds? Work–family–school role conflicts were negatively correlated with job satisfaction among the registered nurses pursuing a further degree in China. Work‐related social support significantly moderated the relationship between work–family–school role conflicts and job satisfaction among registered nurses pursuing a further degree. The implication of this paper: Certain policies such as work flexibility, shift work and part‐time work that are family‐ and school‐friendly could be instituted by hospital administrators to mitigate the effect of work–family–school role conflicts on job satisfaction among RNs pursuing further degrees. When facing work–family–school role conflicts, registered nurses pursuing further degrees should ask for help from department managers or coworkers in order to alleviate their work–family–school role conflicts and improve their job satisfaction.